Subthreshold Photocoagulation, Laser Endpoint Management Based on Optical Coherence Tomography Angiography in Cases of Diabetic Macular Edema Refractory to Anti-VEGF - Karasu, Bugra; Akbas, Yusuf Berk; Aykut, Aslan; Çelebi, Ali Riza Cenk (Klinische Monatsblätter für Augenheilkunde, 2022)
Purpose This study aimed to determine the changes that occur in the vasculature, as based on optical coherence tomography angiography (OCTA) after non-damaging endpoint management (EpM), using a continuous wave yellow laser. The study was on eyes with diabetic macular edema (DME) that were resistant to anti-vascular endothelial growth factors (anti-VEGFs).Materials and Methods This was a retrospective analysis of OCTA images of 44 eyes in 44 patients with DME refractory to anti-VEGF. The eyes were treated with a PASCAL Streamline yellow laser (577 nm wavelength, 200 mm spot size). Treatment was administered to the DME area and utilized 10% continuous wave laser energy and 0.50 µm beam diameter spot spacing. Best-corrected visual acuity (BCVA) and enhanced in-depth imaging with optical coherence tomography (EDI-OCT) and fundus autofluorescence (FAF) images were recorded at baseline, and 3 and 6 months posttreatment. Total choroidal area (TCA), luminal area (LA), stromal area (SA), and the choroidal vascularity index (CVI) were calculated using Image J software. The macula was divided into five quadrants in accordance with the mapping system in the Early Treatment Diabetic Retinopathy Study (ETDRS).Results All patients (mean age: 58.90 ± 9.55 years) were diagnosed with diabetes mellitus type 2. Mean BCVA at baseline was 0.30 ± 0.11 logarithm of the minimum angle of resolution (logMAR) versus 0.23 ± 0.10 logMAR at 3 months (p = 0.032) and 0.17 ± 0.10 logMAR at 6 months (p = 0.013). The foveal avascular zone area (FAZ) decreased in the deep capillary plexus (DCP) from baseline to 6 months (p = 0.028). Vessel densities (VDs) of the superficial capillary plexus (SCP), DCP, and choriocapillaris decreased significantly in the fovea at 3 and 6 months compared to baseline (p < 0.05 for both follow-up time points). There were significant decreases in SCP and DCP in the superior quadrant at the end of month 6 (p = 0.001 and p = 0.038, respectively). There was a significant decrease in the nasal quadrant of the DCP and choriocapillaris at the end of month 6 (p = 0.024 and p = 0.049, respectively). Although there was a significant decrease in central macular thickness (CMT) (p < 0.001), subfoveal choroidal thickness (SFCT) (p < 0.001), and LA (p = 0.034) at months 3 and 6, there was no significant change in the CVI (p = 0.19). According to the DME recovery rate, 36 eyes (81%) were irradiated once, whereas 8 eyes (19%) were irradiated twice.Conclusions Non-damaging EpM therapy using a continuous wave yellow laser in eyes with DME that are resistant to anti-VEGFs induces significant changes in the SCP, choriocapillaris, and, most commonly, the DCP, which caused a significant decrease in VDs during 6 months of follow-up.
Keywords: non-damaging EpM yellow laser; anti-VEGF-resistant diabetic macular edema; optical coherence tomography angiography; choroidal vascularity index